Children's Song Trio As A Form Of Controlling Gadget Use In Children - Tiantaraputra, Riosa Oktaf (Repertoar, 2025)
Art research represents the diversity of perspectives that come from the art disciplines of each practitioner as an effort to continue to establish the principle of usefulness. Looking at the younger generation, especially children who from time to time experience changes in learning patterns to parenting patterns, art is considered capable of strengthening these patterns in order to maintain a balance so that relatively minor impacts occur. This includes the use of technology by children, which tends to be less wise, thus risking affecting their future. Technology, in this case, gadgets, has become an important tool to support children in learning. However, the use of gadgets in children is often uncontrolled due to a lack of parental supervision, so that negative impacts are very likely to occur. This control effort starts from qualitative analysis and quantitative data collection in the form of questionnaires distributed to respondents of elementary school children. Based on these efforts, valid data was found, and an agreement was made to make children's songs a tangible manifestation of efforts to control the use of gadgets in children. Children's songs are expected to be an important part of the success of a civilisation, so that children's participation continues to be optimal without being tainted by the negative impact of gadgets.